Design and Experiment on Self-propelled Precise Feeding Equipment for Dairy Cow - Hewei Meng; Zhenjiang Gao; Xiaoling Luo; Za Kan; Hai Lin (Institute of Advanced Engineering and Science, 2013)
Designed a kind of self-propelled precise feeding machine for single dairy cow based on the technology of RFID, to achieve the automation,fine and intelligent of dairy farming.The computer was used as the information management platform, MCU was used as control platform, even using wireless transmission, RFID recognition, infrared detection technology and so on, which achievement the information data of wireless transmission,precise recognition and detection cattle position.It is applied to equal-diameter and variable-pitch screw feeding structure to realize the precise concentrated feed supply, equipment performance test shown that the system speed 60rpm is the most stable when feeding, feeding accuracy not less than 97.5%, to meet the feeding requirements, equipped with the best traveling speed is 0.6m/s, the response time of the system is 0.4s, the recognition rate is 96%; through one-month feeding experiment in the dairy cow farm showed that the milk production was increased, the average daily milk yield of individual cows improve 0.8kg than artificial feeding. DOI: http://dx.doi.org/10.11591/telkomnika.v11i4.2357